Contributions of argumentative semantics for the delineation of the expression of the preterite perfect in Spanish - Araujo, Leandro Silveira de [UNESP] (Univ Sao Paulo, Fac Filosofia, 2017)
This paper presents some contributions of argumentative semantics to the study of the functioning of the perfecto simple (PPS) and compuesto (PPC) in Spanish. With this purpose, we discuss how this discipline conceives the argumentation and inserts it into the linguistic system. Next, we find in the Argumentative Operator concept a strong evidence that the linguistic elements present a value that indicates the argumentative direction that can be constructed in an utterance. From this theoretical framework, we show how, in some situations, the PPS and the PPC lead to different argumentative positions, functioning, therefore, as Argumentative Operators. In addition, we evaluate the applicability of Benveniste (2005) and Weinreich (1968) proposals for the study of verbal temporality from the perspective of communicative intentionality, to support the hypothesis that the use of one form or another can be defined by argumentative issues..
Keywords: compound perfect; simple perfect; Spanish; argumentative semantics; argumentative operators